Peran Media Sosial Instagram dalam Mempublikasikan Dakwah Majelis Az-Zikra Sentul Bogor - Saifuddin, Saifuddin; Syafrin, Nirwan; Syarah, Maya May (Komunika: Journal of Communication Science and Islamic Dakwah, 2020)
In this modern era, there are a lot of media that can be used as a means of disseminating information and can be accepted by all groups. And one of the most popular uses of social media is Instagram. Az Zikra Assembly Sentul Bogor is one of the largest assemblies in Indonesia that uses social media Instagram as a means of spreading da'wah messages with the @azzikramediaofficial account. By utilizing the features found on Instagram, the @azzikramediaofficial account can create content or disseminate Islamic messages effectively and easily accepted by other Instagram users. The purpose of this study is to dig deeper and understand the role of Instagram social media in publishing da'wah. In this research, the method used is qualitative with a case study approach. Data collection techniques used are observation, interviews and documentation. The findings from this study explain that the Assembly of Az Zikra Sentul Bogor with the Instagram account @azzikramediaofficial often uses the Live Streaming feature, IG TV, photos, videos and stories in disseminating da'wah messages. In addition, the content of the material posted is about Islamic knowledge in everyday life. The positive impact that was felt by the Az Zikra Sentul Bogor Council after using social media Instagram as a propaganda medium was that it was easy to reach all congregations from various groups in remote areas. What is really felt at this time is being able to continue preaching even in the midst of the corona pandemic like now. The positive impact that was felt by the Az Zikra Sentul Bogor Council after using social media Instagram as a propaganda medium was that it was easy to reach all congregations from various groups in remote areas. What is really felt at this time is being able to continue preaching even in the midst of the corona pandemic like now. Abstrak Di zaman modern ini banyak sekali media yang bisa dijadikan sebagai sarana penyebaran informasi dan bisa diterima oleh semua kalangan. Dan salah satu penggunaan media sosial yang populer adalah instagram. Majelis Az Zikra Sentul Bogor merupakan salah satu Majelis terbesar di Indonesin yang menggunakan media sosial instagram sebagai sarana menyebarkan pesan-pesan dakwah dengan akun @azzikramediaofficial. Dengan memanfaatkan fitur-fitur yang terdapat pada instagram, akun @azzikramediaofficial dapat membuat konten atau menyebarluaskan pesan-pesan Islamiyah secara efektif dan mudah diterima oleh pengguna instagram lainnya. Adapun tujuan penelitian ini adalah untuk menggali lebih dalam dan memahami tentang peran media sosial instagram dalam mempublikasikan dakwah. Dalam penelitian ini metode yang digunakan adalah kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Hasil temuan dari penelitian ini menjelaskan bahwa Majelis Az Zikra Sentul Bogor dengan akun instagram @azzikramediaofficial sering menggunakan fitur Live Streaming, IG TV, foto, video dan story dalam menyebarluaskan pesan-pesan dakwah. Selain itu konten materi yang di post adalah mengenai pengetahuan Islami dalam kehidupan sehari-hari. Dampak positif yang dirasakan oleh Majelis Az Zikra Sentul Bogor setelah menggunakan media sosial instagram sebagai media dakwah adalah mudahnya menjangkau semua jemaah dari berbagai kalangan dib pelosok daerah. Yang sangat dirasakan pada saat ini adalah bisa tetap berdakwah walaupun ditengah pandemi corona seperti sekarang. Dampak positif yang dirasakan oleh Majelis Az Zikra Sentul Bogor setelah menggunakan media sosial instagram sebagai media dakwah adalah mudahnya menjangkau semua jemaah dari berbagai kalangan dib pelosok daerah. Yang sangat dirasakan pada saat ini adalah bisa tetap berdakwah walaupun ditengah pandemi corona seperti sekarang.